THE USE OF VIDEO IN TEACHING LISTENING SKILL - Arjulayana Arjulayana (Globish: An English-Indonesian Journal for English, Education, and Culture, 2018)
ABSTRACT The objective of this research is to give understanding and clear explanation about teaching students’ listening skill by English video. Commonly, teaching listening through tape recorder, but in this research teacher shows different way, video is collaboration between pictures and sound components, and it contains a recording of a movie or television program. Students can be able to know the activity or a topic being discussion through visual aid and knowing the pictures expression clearly, this way can help students to get clear information both pronunciations and expression. Grade VIII of SMPN 15 Tangerang with total number is 20 students and 10 English teachersas the subject of the research.  Qualitative descriptive method is applied in this research to explain teaching process through video clearly, however, literature and questionnaere with close answer form is given to get the data. The result of this research are: firstly, teaching listening skill through video can be used by the teacher to make a listening class is more enjoyable and understandable, because audio visual aid can cover students various learning style, finally at the end of teaching and listening process the objectives of study can be gained. Secondly; teaching listening through video is very useful way to encourage and foster students’ listening skill and their interest.      Keywords: Using Video, Listening skill, teaching listening